Effect of tamarillo (Cyphomandra betacea Sendtn.) seed ethanol extract on HSC-3 tongue cancer cells - Saqila Salfabila; Janti Sudiono (Wolters Kluwer Medknow Publications, 2022)
Background: Cancer is characterized by abnormal cell growth. Squamous cell carcinoma is the most common type oral cancer. Tamarillo fruit extract shows antiproliferative and antioxidant activity against breast cancer (MDA-MB-231) and liver cancer (HepG2) cells in rat models. Tamarillo seed extract consists of phenolics, flavonoids, triterpenoids, tannins, and alkaloids, which have antioxidant, antiproliferative, anti-inflammatory, and anticancer activity. Objectives: The aim of this study was to determine the effect of tamarillo seed ethanol extract at different concentrations on the viability of a tongue cancer cell (human oral squamous carcinoma cell line HSC-3). Methods: This experimental in vitro laboratory study comprised a treatment group comprising HSC-3 cells treated with eight concentrations of tamarillo seed extract (8, 4, 2, 1, 0.5, 0.25, 0.125, and 0.0625 μg/µL) and a positive control group treated with 3% H2O2. Shapiro-Wilk test showed that the data were distributed normally with P > 0.05. One-way analysis of variance (ANOVA) test showed that there were significant differences among concentrations group of the extract on HSC-3 viability cells with P ≤ 0.05. Results: At a concentration of 2 μg/µL, tamarillo seed ethanol extract showed the highest cytotoxicity against HSC-3 cells. Post hoc test revealed a significant difference (P < 0.05) in cell viability of concentration 2 μg/µL compared with that of the lower concentrations (0.25, 0.125, and 0.0625 μg/µL) and the positive control but there was no significant difference with those of higher concentration (4 and 8 μg/µL). Conclusions: A low concentration of tamarillo seed ethanol extract (2 µg/µL) had the highest cytotoxicity against HSC-3 cells significantly reducing cell viability. However, this concentration was not able to surpass the inhibition ability of the positive control (3% H2O2).